Minor Hygieia. Iconographic Aspects of the Goddess in the Numismatic and Glyptic (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
This study aims at analyzing the different iconographic aspects of goddess Hygieia in Greek coinage and glyptic. For this purpose the coins and gems bearing the goddess’ representation have been divided into different iconographic typologies, inside which a careful examination of her iconographic attributes has been developed. The intent is to show, where possible, the symbolism and meanings that were attributed to these various images. Numismatic often allows to attest the presence of sanctuaries specifically dedicated to Hygieia in the different poleis and it shows how the Roman emperors and empresses, as long as their public life was concerned, frequently associated their own image with that of the goddess according to specific motivations, not least political ones. On the other hand, glyptic allows to point out how the image of Hygieia was employed in private life with a propitiatory purpose.
Keywords: Hygieia; numismatics; glyptic; iconography; Asclepius